Active Self-Organization of Actin-Microtubule Composite Self-Propelled Rods - Farhadi, Leila; Fermino Do Rosario, Carline; Debold, Edward P.; Baskaran, Aparna; Ross, Jennifer L. (Frontiers in Physics, 2018)
Spontaneous self-organization of active matter has been demonstrated in a number of biological systems including bacteria, cells, and cytoskeletal filaments. Cytoskeletal filaments act as active polar rods when they are propelled along a glass surface via motor proteins. Actin has previously been shown to display polar or nematic ordering, whereas microtubules have been shown to create large vortices. For the first time, we combine both the actin and microtubule gliding into a composite active system. In the absence of actin filaments, microtubule filament organization transitions from isotropic to nematic to polar as a function of filament density. We find that the presence of a crowder, methylcellulose, is essential for this transition. In the absence of microtubules, actin transition from isotropic to nematic. In combination, microtubules are affected by the presence of actin and the overall density of the filaments, becoming entrained with the nematic alignment of actin. Actin filaments are not as affected by the presence of microtubules. These results serve as first step in exploring the rich emergent behavior that can result from composite active matter system with tunable particle properties, self-propulsion speeds, and interparticle interactions.